Randomly amplified polymorphic dna (RAPD) and connexin-26 gene sequence analysis of non-syndromic heredofamilial hearing loss - Saad, M. M.; Mohamad, N. A.; Mohamad, G. I. A.; Mohamad, H. A. (2007)
Hearing loss is a multifactorial disorder resulting from both genetic and environmental factors. About 90 to 100 genes were identified for non-syndromic heredofamilial sensorineural hearing loss. Among different known genes, Connexin-26 gene mutations are reported to be re-sponsible for half of all hereditary hearing loss in many countries. A single known mutation, 35 delG, is the most common mutation in Connexin-26 gene. The pre-sent study aimed to identify the patterns resulting from Randomly Amplified Polymorphic DNA (RAPD) analysis, to search for specific band(s) that character-ize genes affecting hearing, and to detect mutations in Connexin-26 gene resulting in heredofamilial hearing loss. DNA isolation was carried out for fifteen patients and seven healthy rela-tives and subjected to RAPD-PCR analysis. Eleven patients were subjected to Connexin-26 gene sequencing. Gene se-quencing of Connexin-26 reveals muta-tion in only one patient, which, suggests that mutations other than Connexin-26 genes may be implicated in non-syn-dromic heredofamilial hearing loss in Upper Egypt. The dendrogram, that fol-lowed RAPD analysis, classified patients into three groups, suggesting the presence of three possible mutations responsible for this type of hearing loss. Complete analysis of the obtained bands revealed that band 485 bp is the only one existing in all examined patients and relatives, while the other 35 bands are polymorphic. Some bands (965, 950, 730 and 80 bp) are absent in all seven relatives, but present in some of the affected patients. These bands can be used as diagnostic bands, as their presence can identify patients with non-syndromic heredofamilial hearing loss.
Includes references.
1
Keywords: Deafness, Noise induced; Hearing levels; Connexins